(untitled) (Вестник транспорта - Transport xabarnomasi, 2025)
The article examines the role of the station duty officer in managing train traffic and shunting operations. The problems associated with the subjectivity of decision-making, the lack of clear regulations and centralized control systems are identified. Measures are proposed to automate the process of distributing cars using mathematical algorithms and set theory. An analysis of possible combinations of delivering cars to freight facilities and minimizing their waiting time is conducted. Using the example of the Zavodskaya station, the effectiveness of the modeled formulas is demonstrated, which made it possible to reduce the idle time of cars.